ORGANIC FERTILIZER RESPONSE AND ANORGANIC FERTILIZER ON GROWTH AND PRODUCTIVITY OF DRAGON FRUITS - Azri Azri (Agros Journal of Agriculture Science, 2018)
The low production of dragon fruits in West Kalimantan is one of them caused by low soil fertility. Fertilization is one effort to improve soil fertility. This research was conducted with the aim to study fertilizer technology that can increase dragon fruit production. The treatments consist of: P0: no fertilizer, P1: 150 g per plant, P2: 300 g per plant, B0: no manure, B1: manure 10 kg per plant, B2 = manure 20 kg per plant. The study used Randomized Block Design in factorial with three replications. The results showed that the provision of organic and inorganic fertilizers have a positive effect on the growth and production of dragon fruit plants, giving organic fertilizers and inorganic real increase the number of fruit and dragon fruit production. Fertilization with 300 g NPK + 10 kg manure produces the best fruit and dragon fruit production. Dragon fruit cultivation in West Kalimantan is economically feasible to be developed with B / C ratio of 1.22 and 1.32.